Mechanism and Applications of Electrical Stimulation Disturbance on Motoneuron Excitability Studied Using Flexible Intramuscular Electrode. Issue 7 (7th May 2019) - Wang, Jiahui; Wang, Hao; Lee, Chengkuo
Abstract: Wearable and implantable devices are irreplaceable components in the modern healthcare system. Electrical stimulation on the nervous and neuromuscular system, as a way of therapeutic interventions, has been widely applied to people with neurological disorders and neuromuscular disabilities. The conventional way to study electrical stimulation on the skeletal muscle employs single‐channel wire electrodes, which have limited capability to explore the complicated motoneuron distribution in muscle tissue. Here, a microfabricated flexible multiple‐channel intramuscular electrode is presented, which enables the study of electrical stimulation using electrode sites of different spatial arrangements with respect to the motoneuron distribution. Observations are reported on slow disturbance on motoneuron excitability induced by large‐distance electrodes targeting at the end motor nerves, as well as fast disturbance induced by small‐distance electrodes targeting at the main motor nerve trunk. The phenomena of slow and fast disturbance have different potential applications in the field of neuromodulation. In the case of slow disturbance, force output is predictable and shows gradual change, which is suitable for accurately controlled functional electrical stimulation (FES). For fast disturbance, the disappearance of force output opens the possibility for muscle conduction block applications, which can be used for treatment of muscle sparsity by blocking the involuntary motor intentions. Abstract : A flexible intramuscular electrode is successfully used to explore various spatial interaction between stimulation electrodes and motoneurons. Slow and fast disturbance on motoneuron excitability are observed. Slow disturbance stimulation generates force output with gradual change and is suitable for functional electrical stimulation applications. Fast disturbance stimulation induces force output with abrupt change and opens the possibility for muscle conduction block applications.